พฤติกรรมของผู้บริโภคในจังหวัดเชียงใหม่ในการใช้บริการโรงพยาบาลเอกชน - วรรณี ศรีพรหม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study was to study behavior of consumers in Chiang Mai Province towards using private hospital services. The data was collected by questionnaire distributed to 300 samples. The data was then analysed using descriptive statistics, namely frequency, percentage and mean, as well as t-test and ANOVA. The results of the study showed that the number of male and female samples is equal and most were single. Most held Bachelor’s degree with monthly income of 10,001-30,000 baht. They were 21-30 years old and were private company employees the most. From the study of the consumers’ behaviour, it was found that the reason for using private hospital services was for the convenience and fast service. The days and times that they used the services were not consistent. They made the decision to use the services by themselves. They paid for the services by themselves. They obtained information about the services from friends, relatives, and acquaintances. From the study of marketing mix, it was found that the consumers ranked the following sub-factors as the highest in each category. For product and service, it was the expertise of the medical personnel. For personnel, the staff was friendly and polite. For process, the treatment was effective. For physical construction and presentation, the hospital was clean. For place, the hospital was conveniently situated. For marketing promotion, the public relations staff was efficient in giving information. For price, the expenses were reasonable and affordable. When analysing personal information, namely gender, age, income, and means of payment, it was found that consumers with different gender, age, income, and means of payment ranked some sub-factors at different levels, at the statistical significance of 0.05.